EFFECT OF THYME LEAVES ON SOME PHYSIOLOGICAL PARAMETERS , TISSUE CHEMICAL COMPOSITION AND LIPID PROFILE IN MALE AND FEMALE LOCAL RABBITS - Khalid Hassani Sultan (Mesopotamia Journal of Agriculture)
This study was designed to investigate the effects of Thyme leaves ( Thymus vulgaris ) on some physiological parameters and lipid profile , tissues chemical composition , body components in male and females local rabbits . The rabbits ( 12 weeks old ) were divided into 4 groups 6 rabbits each ( 2 replicates ) for males and females . 1st group ( males ) and in the 2nd group ( females ) were given the standard ration ( control ) , the 3rd ( males ) and the 4th ( females ) groups were given standard ration containing 2 % thyme leaves for 10 weeks . Blood and tissue samples were obtained at the end of 10th week.The results revealed a significant decrease in W.B.C and R.B.C , hemoglobin con. , p.c.v. in both sex , the decrease in males was significant as compared with females , Thyme leaves produced a significant increase in M.C.H, M.C.H.C. in both sex .Also the Thyme leaves caused a significant decrease in Cholesterol levels in both sexes , the decrease in females was significant, also caused a significant increase in Triglyceride in both sexes, the increase in males was significant , HDL – C significantly increased , while LDL – C was decreased , in both sexes , the improvement was better in males . These alteration in HDL – C,LDL – C were reflected in a significant improvement of risk ratio.The treatment causes a significant increase in dry matter , fat % in liver and heart tissues in both sexes , while the thigh tissue showed a significant increase in fat % only. Also there was a significant increase in visceral and shoulders fat % in both sexes , and a significant increase in females carcass weight .